2018
DOI: 10.1128/mbio.00972-18
|View full text |Cite
|
Sign up to set email alerts
|

A Proteolytic Complex Targets Multiple Cell Wall Hydrolases in Pseudomonas aeruginosa

Abstract: Carboxy-terminal processing proteases (CTPs) occur in all three domains of life. In bacteria, some of them have been associated with virulence. However, the precise roles of bacterial CTPs are poorly understood, and few direct proteolytic substrates have been identified. One bacterial CTP is the CtpA protease of Pseudomonas aeruginosa, which is required for type III secretion system (T3SS) function and for virulence in a mouse model of acute pneumonia. Here, we have investigated the function of CtpA in P. aeru… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(104 citation statements)
references
References 57 publications
(78 reference statements)
8
92
0
Order By: Relevance
“…MepM1 (YebA, PA0667) belongs to a group of murein endopeptidases (EPs) which putatively modulate PG cross-linking (43). A study revealed that the protease CtpA (PA5134) inactivates various EPs, namely, those encoded by PA0667 (TUEID40_04290 or mepM1), PA4404 (TUEID40_02316), PA1198 (TUEID40_01415), and PA1199 (TUEID40_ 01414), and thereby controls the level of PG cross-linking (43). TUEID40_01415 also showed reduced read counts upon treatment with MEM and/or FEP, but to a much lesser extent than MepM1 did (Data Set S3).…”
Section: Resultsmentioning
confidence: 99%
“…MepM1 (YebA, PA0667) belongs to a group of murein endopeptidases (EPs) which putatively modulate PG cross-linking (43). A study revealed that the protease CtpA (PA5134) inactivates various EPs, namely, those encoded by PA0667 (TUEID40_04290 or mepM1), PA4404 (TUEID40_02316), PA1198 (TUEID40_01415), and PA1199 (TUEID40_ 01414), and thereby controls the level of PG cross-linking (43). TUEID40_01415 also showed reduced read counts upon treatment with MEM and/or FEP, but to a much lesser extent than MepM1 did (Data Set S3).…”
Section: Resultsmentioning
confidence: 99%
“…Our data are consistent with direct interaction between CtpA and the prodomain. However, because it is likely that CtpA has multiple degradation targets, some of which may include homologs of identified target peptidoglycan hydrolases, it is possible that CtpA is necessary for prodomain degradation due to indirect effects, such as cleavage of another protein or changes in the peptidoglycan (Singh et al, 2015;Srivastava et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Size of 250 kDa protein standard is indicated at right. [Colour figure can be viewed at wileyonlinelibrary.com] as the CtpA substrate (Srivastava et al, 2018). Multiple observations suggest that a third, unidentified protease (P3) is responsible for removing C-terminal residues to convert FhaB into a CtpA substrate.…”
Section: An Unknown Protease Removes the Ect To Allow Ctpa-dependent mentioning
confidence: 99%
“…We recently described a mesocosm system in which SPF mice are 'rewilded' through 70 controlled release into an outdoor enclosure facility (7). A key feature of the enclosure is that a 71 zinced iron wall excludes predators and rodents harboring disease-causing infectious agents, 72 while allowing exposure to natural soil, vegetation, and weather.…”
Section: Main Text 51mentioning
confidence: 99%
“…A key feature of the enclosure is that a 71 zinced iron wall excludes predators and rodents harboring disease-causing infectious agents, 72 while allowing exposure to natural soil, vegetation, and weather. Mice rewilded through transient 73 release into the enclosure acquire a bacterial microbiota characterized by increased diversity, and 74 display heightened susceptibility to helminth infection (7). To determine the consequence of 75 microbial colonization in the natural environment on the steady-state immune system, we applied 76 multicolor flow cytometry to analyze the immune cell composition of blood and mesenteric 77 lymph nodes (MLNs) from SPF mice aged 6-8 weeks old at the time of release into the enclosure 78 and captured 6-7 weeks later, herein referred to as rewilded mice.…”
Section: Main Text 51mentioning
confidence: 99%